Effects of surgically assisted rapid maxillary expansion on mandibular position: a three-dimensional study - Talles Fernando Medeiros Oliveira; Valfrido Antônio Pereira-Filho; Mario Francisco Real Gabrielli; Eduardo Sanches Gonçales; Ary Santos-Pinto (SpringerOpen, 2017)
Abstract Background This study aimed to evaluate three-dimensional changes in mandibular position after surgically assisted rapid maxillary expansion (SARME). Methods A retrospective study was carried out with tomographic records of 30 adult patients with maxillary transverse deficiency who underwent SARME. Cone beam computed tomography scans were obtained preoperatively (T1), after expansion (T2) and 6 months after expansion (T3). Mandibular landmarks were measured with respect to axial, sagittal, and coronal planes. Repeated measures ANOVA was used for statistical analysis. Results Clockwise rotation and lateral displacement of the mandible were observed immediately after SARME. However, mandibular displacements tended to return close to their initial values at T3. Conclusions Clockwise rotation and lateral shift of the mandible are transient effects of SARME.